Density and viscosity of aqueous mixtures of N-Methyldiethanolamines (MDEA) and ionic liquids - Yusoff, R.; Aroua, Mohamed Kheireddine; Shamiri, A.; Ahmady, A.; Jusoh, N.S.; Asmuni, N.F.; Bong, L.C.; Thee, S.H. (American Chemical Society, 2013)
The density and viscosity of aqueous mixtures of N-methyldiethanolamine (MDEA) and the ionic liquids (ILs) 1-n-butyl-3-methylimidazolium tetrafluoroborate (bmimBF4), 1-butyl-3-methylimidazolium dicyanamide (bmimDCA), and 1-ethyl-3-methylimidazolium trifluoromethanesulfonate (emimOTf) were determined. The measurements were carried out at 1 atm pressure and temperatures ranging from (303.15 to 363.15) K. The concentration of MDEA was fixed at (2.0 and 4.0) M, whereas the IL concentration was varied from (0.5 to 2.0) M. Both densities and viscosities were increased with increasing IL concentration. Correlation equations of density and viscosity for pure substances and for MDEA and ILs aqueous mixtures as a function of temperature and concentration of MDEA and ILs were also determined. The linear correlation for density had an excellent accuracy with less than 0.98 % deviation for all aqueous mixtures of MDEA and ILs. Meanwhile, the extended Arrhenius equation for viscosity achieved acceptable precision with less than 30 % of deviation from experimental data except for 2.0 M MDEA and 1.5 M bmimDCA mixtures.